MOTIVATION AND SELF-CONFIDENCE AS PREDICTORS OF SPEAKING FLUENCY AND ACCURACY IN EFL CONTEXTS - KUSMARTINI, SRI ENDAH (Politeknik Negeri Sriwijaya, 2025)
Effective communication is vital for humans as social beings, especially in EFL contexts. Speaking skills such as fluency and accuracy are essential, and emotional factors like motivation and self-confidence significantly influence learners’ performance. Although these predictors are widely recognized, their relationships with speaking proficiency are interpreted differently across studies, indicating a need for further research to develop an effective instructional model. This study adopted a quantitative correlational approach to investigate the associations between motivation and self-confidence as predictor variables, and speaking fluency and accuracy as outcome variables, both individually and collectively. Data were collected from 60 respondents through questionnaires and analyzed using descriptive statistics, Pearson correlation, and linear regression. Results indicated a moderate correlation between motivation and speaking fluency (r = 0.406), and between self-confidence and fluency (r = 0.559). For speaking accuracy, motivation showed a low correlation (r = 0.324), while self-confidence had a moderate correlation (r = 0.491). Simultaneously, the predictors showed moderate correlations with fluency (R = 0.559) and accuracy (R = 0.493). The influence values were 0.313 for fluency and 0.243 for accuracy, indicating that motivation and self-confidence contributed 31.3% and 24.3% to students’ speaking fluency and accuracy, respectively.